(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Oncology is a crucial branch of medicine focused on the detection, treatment, and prevention of cancer. Innovative medical tools and technologies play a key role in early detection and effective treatment of cancer. Tools used in oncology help with diagnosis, treatment, and monitoring. This article provides an overview of some of the key tools used in oncology, their operating principles, and practical applications.